PROFILE OF COGNITIVE STRUCTURE OF STUDENTS IN UNDERSTANDING THE CONCEPT OF REAL ANALYSIS - Wahyu Widada (IKIP Siliwangi and I-MES, 2016)
The purpose of this research is to describe proil cognitive structure of students in understanding the concept of real analysis. This research is part of the research development of the theory of cognitive structure of students Mathematics Education Program at the University of Bengkulu. The results of this research are: 1)there are seven models decompositions of genetic students mathematics education reviewed based on the SRP Model about the concepts of Real Analysis namely Pra-Intra Level, Level intra, Level semi-inter, Level inter, Level semi-trans, Trans Level, level and Extended-Trans (only theoretic level while empirically not found); 2) There are six models decompositions of genetic students mathematics education reviewed based on KA about the concepts of Real Analysis namely Level 0: Objects of concrete steps; Level 1: Models Semi-concrete steps; Level 2: Models Theoretic; Level 3: Language in Domain Example; Level 4: Mathematical Language; Level 5: Inferensi Model. Profile of cognitive structure of mathematics education student at the University of Bengkulu is 6.25% Students located on the Basic Level (Pra-Intra Level with concrete objects), there is 8.75% Students located at Level 0 (intra Level with concrete objects), there are 15,00% Students located at Level 1 (semi-Level inter with Semi-Concrete Model), there are 33.75 percent students located on Level 2 (Level inter with theoretical model), there are 22.50 percent students located at Level 3 (Semi-trans Level with the Bible in Domain example), there are located on the student percent during the Level 4 (Trans Level with the language of Mathematics), and there are 0 percent students located at Level 5 (Level Extended-Trans with Inferensi Model). Students Education Mathematics at the University of Bengkulu pembangunnya element is functional can achieve Trans Level, students will be able to set up activities and make the algorithm that formed the concept/principles with the right. Functional students can also perform the process of abstraction using the rules in a system of mathematics.